2020
DOI: 10.14238/pi60.2.2020.97-101
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Growth Diagrams Of Indonesian Children to 2006 World Health Organization Growth Standards in diagnosing stunting

Abstract: Background Stunting represents a linear growth disturbance due to chronic malnutrition, recurrent infection, and inadequate psychosocial stimulation. The 2006 World Health Organization (WHO) Growth Standards are utilized as a modality in monitoring children’s growth, but to date, there has been no recommendation on use of the Growth Diagrams of Indonesian Children to monitor the growth of Indonesian children. Objective To determine the proportion of stunting, the sensitivity and specificity of Growth Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…A previous study found that the proportion of stunting was significantly lower using the Growth Diagrams of Indonesian Children compared to the 2006 WHO Growth Standards (36.2% to 46.8%, respectively; P<0.001). 9 Furthermore, a study reported that Indonesian boys (SD 1.47) and girls (SD 1.43) were lower in height compared to American children. 6 The Growth Diagrams of Indonesian Children had good specificity (98.66%) for diagnosing stunting in the Indonesian pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study found that the proportion of stunting was significantly lower using the Growth Diagrams of Indonesian Children compared to the 2006 WHO Growth Standards (36.2% to 46.8%, respectively; P<0.001). 9 Furthermore, a study reported that Indonesian boys (SD 1.47) and girls (SD 1.43) were lower in height compared to American children. 6 The Growth Diagrams of Indonesian Children had good specificity (98.66%) for diagnosing stunting in the Indonesian pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…6 The Growth Diagrams of Indonesian Children had good specificity (98.66%) for diagnosing stunting in the Indonesian pediatric population. 9 Nutritional status in the first 1,000 days of life affects future quality of life. Intrauterine growth retardation (IUGR) is a reflection of maternal malnutrition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Provinsi Acehmenempati peringkat ketiga prevalensi stunting tertinggi nasional dan pada anak balita merupakan yang tertinggi, yaitu sebesar 37,9% (Kemenkes 2018). Pada penelitian sebelumnya mencatat prevalensi stunting yang dilakukan pengukuran antropometri dengan kurva pertumbuhan anak Indonesia di Kabupaten Aceh Tenggara dari 141 anak berusia 1-60 bulan adalah sebesar 36,2%, lebih rendah dibandingkan dengan pengukuran menggunakan WHO Growth Standards 2006, yaitu sebesar 46,8% (Wicaksono et al 2020). Hal ini merupakan masalah kesehatan masyarakat yang berat dimana prevalensi stunting disuatu daerah adalah sebesar 30-39% dan masalah yang serius apabila prevalensi stunting = 40% (World Health Organization, 2010).…”
Section: Stuntingunclassified